The effect of menstrual cycle on 2000-m rowing ergometry performance - Forsyth, J. J.; Reilly, T. (European Journal of Sport Science, 2008)
The aim of this study was to examine the effect of menstrual cycle phase on 2000-m rowing ergometry performance. Since high concentrations of oestrogen, indicative of the mid-luteal phase of the menstrual cycle, tend to decrease glycogen utilization and reduce blood lactate concentration, it was predicted that time taken to complete a 2000-m rowing trial would be shorter in the mid-luteal phase. Ten eumenorrhoeic, recreationally trained, female volunteers (mean age 33.0 years, s=7.1) completed 2000-m time trials on a Concept 2 rowing ergometer, in both the mid-follicular and mid-luteal phases of their menstrual cycle. In each phase, a 3-min incremental rowing protocol was used to determine a blood lactate concentration of 4 mmol/l (Tlac-4mM) and maximum oxygen consumption (VO2max); a five-stroke maximal test was used to establish maximal power. Order of testing was randomized for menstrual cycle phase. Variables (Tlac-4mM, VO2max, maximal power) were correlated with speed in the 2000-m time trials, and the effect of menstrual cycle phase on these variables was examined. A blood lactate concentration of 4 mmol/l occurred at a significantly higher mean exercise intensity (mid-luteal vs. mid-follicular: 169.1 W, s=39.1 vs. 159.0 W, s=38.3; P=0.033), heart rate (179 beats/min, s=9 vs. 173 beats/ min, s=11; P=0.0047), and oxygen consumption (2.64 litres · min-1, s=0.66 vs. 2.42 litres/min, s=0.62; P=0.04) in the mid-luteal phase than in the mid-follicular phase. There was no significant difference (P=0.11) in 2000-m time trial speed according to menstrual cycle phase. In conclusion, although Tlac-4mM differed due to menstrual cycle phase, 2000-m rowing performance was unaffected. Further research into the effects of menstrual cycle on rowing performance of a longer duration, among a more homogenous group of females, is recommended.